Study on the metal absorption by two bryophytes from Koyana wildlife sanctuary (India) - and Meena Dongare3, Manda M. Ghatge1, Shakil D. Shaikh2* (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Two bryophyte species Asterella angusta Beauv. and Cyathodium tuberosum Kash. growing across different regions of Koyana wildlife sanctuary have been used as indicators of metal pollution. The estimation of important heavy metals like Cu, Zn, Pb, Ni, Cd and Cr have been carried out in the two bryophyte species using atomic absorption spectroscopy. The low level of metal pollutants was observed in moss specimens collected from the natural habitats and high level in the specimens collected from traffic areas. Overall, Cu and Pb are responsible for causing major pollution in the studied area and the concentration of metals in plant was found to be higher in study region.